Referring Expression in Black Mirror (Season 3 Episode 1: “Nosedive”): Pragmatics Study - Amira Bellita Runadi; Ervina CM Simatupang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to analyze and investigate the various forms of referencing expressions and their meanings in the serial movie Black Mirror: “Nosedive.” The descriptive analysis method was applied in this study. The information used was taken from Charlie Broker's movie scrip. The findings revealed four types of referring expressions, including pronouns (37.5%), proper nouns (25%), indefinite noun phrases (18.75 %), and definite phrases (18.75%). On the other hand, there are three types of meaning: contextual meaning (37.5%), grammatical meaning (37.5 %), and lexical meaning (25%).